Partisipasi Masyarakat Dalam Bidang Ekonomi Melalui Program Pemberdayaan Masyarakat Prodamas Plus di Kelurahan Mojoroto Kota Kediri - aidah, fina nur; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 5 No 1 (2025): JISSOROT, 2025)
The Community Empowerment Program (Prodamas – Program Pemberdayaan Masyarakat) Plus aims to encourage public participation and active role in development at the RT level. This study aims to explain and analyze public participation in the economic sector through the Community Empowerment Program (Prodamas) Plus in Mojoroto Village, Kediri City with a sociological study framework. This study uses a descriptive-explanatory approach because it aims to understand a phenomenon in a more in-depth descriptive manner and uses a theoretical basis to focus on the research topic. The theory used as a scalpel in carrying out this research is the theory of community participation from John M. Cohen and Norman T. Uphoff with four forms division is participation in decision making, participation in implementation, participation in benefits, and participation in evaluation. Based on the results of research conducted by the author, the form of community participation in the decision-making process, namely the community of Mojoroto Subdistrict, is that there are still several areas that are less interested in participating in community meetings, especially in residential areas due to the limited schedules of busy residents. The form of implementation carried out is that residents are not the driving force of the program so that the implementation of development programs does not involve innovations carried out by the community, but remains based on existing Perwali regulations. The results of the forms of benefit taking that can be seen from the economic sector are very diverse, especially the assistance of Joint Business Groups (KUBE – Kelompok Usaha Bersama), namely the first evaluation carried out by the city government, the second carried out by the sub-district, and the third carried out at the sub-district level. Keywords: Prodamas Plus, Empowerment, Public Participation.